Model - Model Pembelajaran Anak Usia Dini - Hilda Zahra Lubis; Nadia Ariqah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Early Childhood Education (ECD) plays a crucial role in forming the foundation of children's cognitive, social, and emotional development. In practice, the selection of the right learning model greatly determines the effectiveness of the teaching and learning process at an early age. The purpose of this study was to examine various learning models applied in ECD education. This research method uses a descriptive qualitative method with literature studies as the main technique, data was collected through a review of journals, books, and educational documents related to ECD learning models such as Cooperative, center models, and area models. The results of the study show that each model has its own advantages, but its effectiveness is greatly influenced by teacher readiness, learning environment, and parental involvement. The implications of this study emphasize the importance of teacher training and curriculum development that is adaptive to children's needs and the characteristics of each learning model. Recommendations are given to educational institutions to select and adapt learning models in the context of supporting overall child development.